Kinerja Usaha Wirausaha Baru (WUB) Sasirangan Di Banjarmasin Pada Masa Pandemi Covid-19 dan Era New Normal - Putri Aulia Emha; Saladin Ghalib (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
ABSTRACT This study aims to determine the supporting and inhibiting factors, strategies and business performance of the new Sasirangan entrepreneurs in Banjarmasin during the COVID-19 pandemic and the new normal era using the 4P aspects, product, price, place, and promotion are aspects of the marketing mix. This research is a qualitative descriptive type using a sample collection technique using snowball sampling with observation and in-depth interviews.Data analysis techniques used are data collection and reduction as well as verification or drawing conclusions. This study uses triangukasu sources and methods to test the validity of the data. In this study, the authors made direct visits to the business actors of WUB Sasirangan in Banjarmasin to conduct interviews.The results showed that the factors that affected the Sasirangan WUB in Banjarmasin were affected during the COVID-19 pandemic, namely the absence of orders, the difficulty of marketing and the availability of raw materials. However, there are other factors that also affect the ability of Sasirangan WUB to survive during the COVID-19 pandemic, namely the provision of training by the relevant agencies to support WUB's performance and the existence of online media that facilitates the buying and selling process. WUB's business performance is more dominant in product and promotion variables. This can be seen from the diversity of products sold by WUB as well as the strategies carried out by carrying out more intensive marketing through online and offline media. Keywords: business performance, marketing mix, business strategy, COVID-19